Proses Islamisasi dan Perkembangan Islam di Kesultanan Banjarmasin - Eliza Eliza; Hudaidah Hudaidah (Program Studi Pendidikan Sejarah Universitas Riau, 2021)
The process of Islamizing the kingdom and the people in the Banjarmasin region was very friendly with the Islamization of Sultan Suryanullah who was known as Raja Samudera and the construction of a sultanate in Banjarmasin. The period of the arrival of Islam in South Kalimantan was related to the connection of the Kalimantan trade route in the trade network of the archipelago which was also an interest of the Banjar Sultanate. This paper is a literature review that discusses the process of Islamization and the development of Islam in Banjarmasin. Regarding the purpose of this religion means examining the process of Islamization and the progress of Islam in the Banjarmasin region. The research method in this paper uses descriptive type research. Islamization in the South Kalimantan region entered through channels, namely Islamization through the da'wah channel, Islamization through political channels, and Islamization through the marriage channel. The peak of Islamic development occurred during the reign of Sultan Tahmidullah II, with the arrival of a Kiai named Muhammad Arsyad al Banjari.